2014
DOI: 10.5194/acp-14-9727-2014
|View full text |Cite
|
Sign up to set email alerts
|

Trace gas emissions from combustion of peat, crop residue, domestic biofuels, grasses, and other fuels: configuration and Fourier transform infrared (FTIR) component of the fourth Fire Lab at Missoula Experiment (FLAME-4)

Abstract: Abstract. During the fourth Fire Lab at Missoula Experiment (FLAME-4, October–November 2012) a large variety of regionally and globally significant biomass fuels was burned at the US Forest Service Fire Sciences Laboratory in Missoula, Montana. The particle emissions were characterized by an extensive suite of instrumentation that measured aerosol chemistry, size distribution, optical properties, and cloud-nucleating properties. The trace gas measurements included high-resolution mass spectrometry, one- and tw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
395
9

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 220 publications
(432 citation statements)
references
References 123 publications
28
395
9
Order By: Relevance
“…Yokelson et al, 1996;Bertschi et al, 2003) and comparable with the reported range of MCE in other studies of high-latitude peats (Yokelson et al, 1997;Stockwell et al, 2014). Emission factors for CO 2 and CO are also typical of smouldering combustion and similar to those from other peat studies, particularly Yokelson et al (1997).…”
Section: Fire Emission Factorssupporting
confidence: 76%
See 2 more Smart Citations
“…Yokelson et al, 1996;Bertschi et al, 2003) and comparable with the reported range of MCE in other studies of high-latitude peats (Yokelson et al, 1997;Stockwell et al, 2014). Emission factors for CO 2 and CO are also typical of smouldering combustion and similar to those from other peat studies, particularly Yokelson et al (1997).…”
Section: Fire Emission Factorssupporting
confidence: 76%
“…Järveoja et al, 2012;Mander et al, 2012;Salm et al, 2012;Strack et al, 2014), (c) no data from ROI or UK peatlands were included in the IPCC derivation, which might mean that the Tier 1 value may not be appropriate for these countries, and (d) no distinction is made between industrial or domestic extraction sites, despite large differences in their drainage, vegetation cover and management characteristics. In addition, previous studies of peatland fire EFs have focused on the boreal peatlands of Alaska (Yokelson et al, 1997) and Canada (Stockwell et al, 2014) and the temperate peatlands of Minnesota (Yokelson et al, 1997) and North Carolina (Stockwell et al, 2014). These studies found that the smouldering combustion of peats associated with low combustion efficiency leads to relatively lower CO 2 emissions (compared with other ecosystems) and much higher carbon monoxide (CO), CH 4 , and other non-CH 4 hydrocarbon emissions.…”
Section: Wilson Et Al: Derivation Of Greenhouse Gas Emission Factmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these studies primarily focused on chemically characterizing gaseous emissions (Benner, 1977;Chen et al, 2007;Christian et al, 2003;Geron and Hays, 2013;May et al, 2014;McMahon et al, 1980;Ward, 1990;Hatch et al, 2015;Stockwell et al, 2015Stockwell et al, , 2014George et al, 2016;Black et al, 2016;Iinuma et al, 2007;Yokelson et al, 1997) while fewer focused on the PM fraction Fujii et al, 2014Fujii et al, , 2015aIinuma et al, 2007). Peatland fire emissions were not considered in the biomass burning emission inventory published by Andreae and Merlet (2001).…”
Section: Introductionmentioning
confidence: 99%
“…Many of these studies primarily focused on chemically characterizing gaseous emissions (Benner, 1977;Chen et al, 2007;Christian et al, 2003;Geron and Hays, 2013;May et al, 2014;McMahon et al, 1980;Ward, 1990;Hatch et al, 2015;Stockwell et al, 2015;Stockwell et al, 2014;George et al, 2016;Black et al, 2016;Iinuma et al, 2007;Yokelson et al, 1997) while fewer focused on the PM fraction Fujii et al, 2014;Fujii et al, 2015a;Iinuma et al, 2007). Peatland fire emissions were not considered in the 5 biomass burning emission inventory published by Andreae and Merlet (2001).…”
mentioning
confidence: 99%